Letters of professor I. V. Popov from his study trip in 1901–1902 to professor S. I. Smirnov: reconstructing their academic relations - Vyacheslav Yachmenik; Denis Kalashnikov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In this publication are presented the letters written by Prof. of Moscow Theological Academy I. V. Popov. The letters of Prof. I. V. Popov, written during the period of his internship in German universities (1901–1902), and addressed to his trusted friend, Prof. of Moscow Theological Academy S. I. Smirnov. These letters are interesting in two respects: on the one hand, because they provide Popov’s impressions of his trip abroad, which throw light on his subsequent academic career, particularly in the field of organization and reform of native theological education; on the other hand, because they reveal the nature of the relationship between the two professors, and clearly show Popov’s intellectual influence on his friend and colleague Smirnov during the preparation of his future dissertation “The Spiritual Father in in the Early Eastern Church” (1906). Popov helps to Smirnov to adjust his view of the chosen research problem, which, according to his original plan, should have concerned a more comprehensive treatment of the sources, and considerably broaden the subject of his research. The published letters are held in the manuscripts department of the Russian State Library in the collection of S. I. Smirnov.